Identifikasi Makroalga yang Tersebar di Perairan Walakiri Sumba Timur - Meiyasa, Firat; Rutung, Meldi Nengi; Amah, Dersi Boru Wala; Manggi, Belandina; Dawu, Asni Meja; Hutar, Marlince Mbati Ana (Jurusan Pendidikan Biologi, Fakultas Ilmu Pendidikan, Universitas Timor, 2023)
This study aims to identify macroalgae scattered in Walakiri waters. The method used in this study was to explore the entire coast of Walakiri. The samples which were then identified visually and morphologically include: color, thallus shape, serrations on the stems of each macroalgae sample and then matched to AlgaeBase: http://www.algaebase.org. The results showed that there were 3 classes of macroalgae with a total of 10 species including red algae (Eucheuma cottonii, Eucheuma spinosum, Achanthopora spicifera), brown algae (Padina australis, Sargassum vulgare, Sargassum cristaefolium, Sargassum polycystum), and green algae (Ulva reticulata, Halimeda micronesica, Codium Fragile). In addition, the water quality of Walakiri is good for macroalgae growth.